MENINGKATKAN KETERAMPILAN MEMBACA MELALUI MEDIA PERMAINAN PAPAN KANTONG PINTAR PADA MATA PELAJARAN BAHASA INDONESIA PESERTA DIDIK KELAS 1 - Ayu Lestari A Daud; Lia Nurhayati; Hendra Saputra S. Adiko (Jurnal Ilmu Pendidikan UMGo, 2025)
The purpose of this study is to improve reading skills through the use of the "Smart Pocket Board" game media for first-grade students at SD Muhammadiyah 2 Limboto. The type of research used is classroom action research, with the research subjects being 19 first-grade students at SD Muhammadiyah 2 Limboto. The research employed observation, tests, and documentation techniques. The data analysis techniques included teacher activity data, student activity data, and student reading skill data. The results of the study showed that during the initial observation, 7 students (37%) demonstrated reading skills. In the first cycle, 13 students (68%) showed improvement, and in the second cycle, 18 students (95%) were skilled in reading. Thus, it can be concluded that the "Smart Pocket Board" game media can improve the reading skills of first-grade students at SD Muhammadiyah 2 Limboto.